The creative eye an artist's guide to unlocking the the mysteries of visual perception - Spears, Heather 1934- (London Arcturus, 2007)
A completely original concept, this title challenges practical artists of every capability and art teachers as never before. It will make them rethink what they see, how they see it, even how they name it, as well as how they reproduce it.
Keywords: Visual perception; Creation (Literary, artistic, etc.).; Art